2012
DOI: 10.26879/298
|View full text |Cite
|
Sign up to set email alerts
|

Error rates and observer bias in dental microwear analysis using light microscopy

Abstract: Despite the increased use of light microscopy in microwear analysis, studies that recognize observer error are scarce. Nonetheless, microwear analysis based on light microscopy may be more prone to observer bias than SEM or confocal microscopy. We measured observer error among five observers, who independently analyzed identical sets of dental wear surfaces on digital micrographs taken through a light microscope. For experienced microscopists, error in light-microscope-based microwear was of a similar magnitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 57 publications
3
62
0
1
Order By: Relevance
“…For these reasons, our goal was not to reproduce absolute feature counts between the two methods, as such is neither possible nor necessary. In user-based microwear methods, relative differences in quantitative variables among taxa is more informative than relying on absolute benchmarks to define dietary differences (Mihlbachler et al 2012). Thus, below we interpret the results from the two techniques separately (in the context of relative differences to other sloths within each technique) and then combine our separate interpretations to hypothesize the feeding ecology of Octodontotherium and Orophodon .…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, our goal was not to reproduce absolute feature counts between the two methods, as such is neither possible nor necessary. In user-based microwear methods, relative differences in quantitative variables among taxa is more informative than relying on absolute benchmarks to define dietary differences (Mihlbachler et al 2012). Thus, below we interpret the results from the two techniques separately (in the context of relative differences to other sloths within each technique) and then combine our separate interpretations to hypothesize the feeding ecology of Octodontotherium and Orophodon .…”
Section: Discussionmentioning
confidence: 99%
“…By quantifying the microwear of species with known diets, a comparative data set can be built and then used to estimate the diet of taxa for which food intake is unknown, including extinct species. Although multiple studies have quantified the microwear of numerous extant mammals whose diet is known, analyses of inter-observer error demonstrate that each investigation of the diet of fossil taxa should develop its own comparative data set74.…”
Section: Methodsmentioning
confidence: 99%
“…As dental microwear records food consumption during the last few days to weeks of an animal’s life, it can be used to clarify ancient diets and assess dietary responses to changing climates and environments. While microwear has been commonly used by anthropologists and paleontologists since the late 1970s (e.g., [13]), the methodologies used to quantify tooth surfaces are highly variable and still debated among researchers, and results generated between and within methods are not directly comparable [47]. …”
Section: Introductionmentioning
confidence: 99%
“…Observer identification and quantification of individual wear features, whether from an SEM micrograph or using light microscopy, is prone to high observer biases, particularly between observers of different experience levels [4,5,7,16]. Grine and co-authors [4] found a 9% error in measurements between observers while Galbany and co-authors [5] found a 6% error in observers with five or more years of experience when quantifying SEM micrographs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation